2018
DOI: 10.1177/0269215518817080
|View full text |Cite
|
Sign up to set email alerts
|

Web-based physiotherapy for people affected by multiple sclerosis: a single blind, randomized controlled feasibility study

Abstract: Objective: To examine the feasibility of a trial to evaluate web-based physiotherapy compared to a standard home exercise programme in people with Multiple Sclerosis (MS). Design: Multi-centre, randomised controlled, feasibility study Setting; Three Multiple Sclerosis outpatient centres Participants: Ninety people with Multiple Sclerosis (Expanded Disability Disease Scale 4-6.5), Interventions: Participants were randomised, to a 6 month individualised, home exercise programme delivered via web-based physiother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 32 publications
0
59
2
Order By: Relevance
“…This participation rate in twice-weekly exercise is comparable to the six-month, multi-center trial (n = 90) with webbasedphysio, except the previously reported multi-center trial included only ambulatory people. 12 Comparing our adherence results with other web-based exercise research in multiple sclerosis is challenging, since methods for defining and measuring adherence are not consistent in the literature. 20 Studies reporting internet-delivered physical activity interventions for people with MS commonly describe physical activity levels measured by self-report questionnaire or…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This participation rate in twice-weekly exercise is comparable to the six-month, multi-center trial (n = 90) with webbasedphysio, except the previously reported multi-center trial included only ambulatory people. 12 Comparing our adherence results with other web-based exercise research in multiple sclerosis is challenging, since methods for defining and measuring adherence are not consistent in the literature. 20 Studies reporting internet-delivered physical activity interventions for people with MS commonly describe physical activity levels measured by self-report questionnaire or…”
Section: Discussionmentioning
confidence: 90%
“…The website contains exercises (videos, text and audio description), which are individually prescribed by a physiotherapist at an initial assessment. 12,13 The physiotherapist is able to review the electronic exercise diaries and remotely alter the exercises in response to comments from participants. The inventory of exercises and the educational materials were previously developed with input from people living with MS in the UK with mild to moderate disability.…”
Section: Intervention Armmentioning
confidence: 99%
“…It is plausible that since this time, the developments in the political landscape surrounding, and the culture of support for, self-management more broadly, have increased. This, coupled with the evolution of digital health in stroke (and in other neurological conditions) such as smart phone applications, telerehabilitation, and telemonitoring [40][41][42][43] for supporting rehabilitation and long-term behavior change, may have impacted on and shifted perceptions about SSM and its implementation somewhat. A secondary analysis approach potentially limited the extent to which broader issues of implementation could have been probed for further exploration in the original focus groups/interviews meaning that some questions may remain unanswered.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Web Based Rehabilitation approaches are an infra-structure that helps all individuals at all ages, including healthy individuals, to guide caregivers and in order to guide multiple sclerosis, rheumatoid arthritis, spinal cord injury, stroke, diabetes mellitus, elderly people, pediatric rehabilitation. 1,[3][4][5] It is estimated that 10% of the global population, about 90% of them live with Type 2 diabetes. Poorly controlled diabetes; There are high risk of complications, including early mortality and cardiovascular disease, nephropathy and retinopathy.…”
Section: Introductionmentioning
confidence: 99%
“…However, for selfmanagement, a Web-based support can relieve some of these barriers (especially in high-income countries with high web access levels). [1][2][3] In people with spinal cord injury (SCI), physical activity and exercise can help maintain muscle strength and flexibility, reduce healing and pain. With the home based, Web rehabilitation approach, it has been determined that exercise programs are effective in improving physical activity in people with SCI.…”
Section: Introductionmentioning
confidence: 99%